CRAFTING NUANCE AND ARTISTRY: THE ROLE OF SYNONYMY AND VARIATION IN LITERARY TRANSLATION (Conferencea, 2024)
The art of literary translation is a nuanced endeavor that involves navigating the intricate landscapes of language, culture, and creativity. This article delves into the profound role of synonymy and variation in literary translation, showcasing how these linguistic tools shape the richness and authenticity of translated works. Through insightful case studies and theoretical frameworks, this exploration sheds light on the intricate artistry that underlies the translator's craft, highlighting the delicate balance between fidelity to the source text and creative adaptation to the target language. By examining the dynamic interplay between synonyms and variations, this article offers a deeper understanding of the transformative power of translation in bridging linguistic and cultural divides.